PENYULUHAN TENTANG PENGELOLAAN BADAN USAHA MILIK DESA DI DESA TELAGA PACA KECAMATAN TOBELO SELATAN KABUPATEN HALMAHERA UTARA - Djiko, Richard (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
This community service activity aims to increase knowledge about Village Owned enterprise planning and development by utilizing village potential. Increase Knowledge about financial administration of Village Owned enterprises. The method used in this activity is counseling, with several stages, namely observation, namely to find out the real conditions in the field, counseling. In this activity those who attended were the Village Owned enterprises Manager, Village Head, Village Consultative Council Members, and Staff of the Telaga Paca Village Office, totaling 34. The results of the field evaluation show that there is an increased understanding of the planning and development of Village Owned enterprises by utilizing the management function. And also there is an increase in understanding related to the financial administration of Village Owned enterprises.